Ovarian Fibroma as a Possible Cause of Fever of Unknown Origin - İkbal Kaygusuz; Ayla Eser; İlknur İnegöl Gümüş; İsmail Kırbaş; Kayıhan Akın; Hacer Haltas; Hasan Kafalı (Gynecology Obstetrics & Reproductive Medicine)
Fibromas are the most common benign solid tumors of the ovary. Clinically, they are asymptomatic and preoperative diagnosis is often difficult. In this paper we report a case of fibroma as a cause of fever of unknown origin (FUO).